2013
DOI: 10.1007/s12665-013-3005-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tracers and indicators bringing together groundwater, surface water and groundwater-dependent ecosystems: importance of scale in choosing relevant tools

Abstract: Groundwater-surface water (GW-SW) interactions cover a broad range of hydrogeological and biological processes and are controlled by natural and anthropogenic factors at various spatio-temporal scales, from watershed to hyporheic/hypolentic zone. Understanding these processes is vital in the protection of groundwater-dependent ecosystems increasingly required in water resources legislation across the world. The use of environmental tracers and indicators that are relevant simultaneously for groundwater, surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…Hydrometric techniques, such as measuring water table depth and discharge, have been successfully used to identify water source and groundwater-surface water mixing [65]. Measurements of variations in groundwater depth can be used in combination with other indicators to identify GDEs because when plant roots are able to access the water table via the capillary zone, diurnal fluctuations in the groundwater depth can be evidence of groundwater uptake by vegetation [66].…”
Section: Ground-based Methods Useful In Identifying Groundwater Depenmentioning
confidence: 99%
“…Hydrometric techniques, such as measuring water table depth and discharge, have been successfully used to identify water source and groundwater-surface water mixing [65]. Measurements of variations in groundwater depth can be used in combination with other indicators to identify GDEs because when plant roots are able to access the water table via the capillary zone, diurnal fluctuations in the groundwater depth can be evidence of groundwater uptake by vegetation [66].…”
Section: Ground-based Methods Useful In Identifying Groundwater Depenmentioning
confidence: 99%
“…Usually, these approaches are helpful and often successful in reaching the aims demanded by guidelines such as the European Commission nitrate directive 91/676/EEC or the European Commission water framework directive 2000/60/EC with the groundwater directive COM (2003)550, but here we want to discuss how much more we can learn and achieve, if we include the micro scale processes in the large-scale considerations. Bertrand et al (2014) demonstrated the usefulness of micro scale investigations for the hyporheic zone, and it is reasonable to hypothesise that a focus on the micro scale will be as informative in groundwater ecosystem s more broadly.…”
Section: Introductionmentioning
confidence: 92%
“…Many techniques exist for measuring GDE–groundwater connectivity, particularly in vegetation and riverine GDEs (Bertrand, Siergieiev, Ala‐Aho, & Rossi, ; Eamus et al, ; Richardson et al, ). These methods include tracers, isotopes and geochemical techniques (Atkinson et al, ), physical techniques using data on hydraulic heads or from fine‐scale radar (Huggenberger, Hoehn, Beschta, & Woessner, ; Lamontagne et al, ), methods comparing proportions of annual water use derived from groundwater (e.g., via evapotranspiration, Eamus et al, ), and statistical modelling or correlative techniques that infer GDE–groundwater connectivity from changes in ecological responses along groundwater gradients such as depth to water table (Elmore et al, ).…”
Section: The Five Steps Of Fergramentioning
confidence: 99%